A Retrospective Investigation of Abortion Storm in Abergele Goats, Waghimira Zone, Amhara Region, Ethiopia - Adane Bahiru; Ayalew Assefa; Biruk Alemu Gemeda; Hiwot Desta; Abebe Tibebu; Abebe Sahle; Barbara Wieland (Scientifica)
A retrospective study was conducted in Abergele and Ziquala districts in Ethiopia to investigate the occurrence, impact, and potential risk factors for abortion in small ruminants linked to a regional abortion storm. Affected (case) and nonaffected (control) villages were compared to assess infectious and noninfectious risk factors causing abortions. A case village was defined as a village with abortion seen in all households enrolled in the study, while a control village is characterized by presence of abortion in two and fewer households. A questionnaire survey, focus group discussions, and serological examinations were used to assess the differences in the abortion rate between the case and control villages. The Rose Bengal Plate Test for Brucellosis, Toxoplasma gondii Antibody Test Kit for Toxoplasma gondii, and ELISA for Chlamydophila abortus and Coxiella burnetii were used to detect antibodies. Per village 15 household flocks were selected. In the case villages, all flocks were affected by abortion (a mean abortion of 13 animals in Abergele and 9 in Ziquala). In contrast, only three households reported abortions in the control villages. A total of 176 blood samples were collected from the case and control villages for further laboratory diagnosis of possible causes of abortion. Of the examined flocks, 17%, 10.2%, and 2.8% were positive for Coxiella burnetii, Toxoplasma gondii, and Chlamydophila abortus, respectively. However, antibodies against Brucella melitensis were not detected. While the seroprevalence was greater for some infectious agents of abortion, there was no significant difference between the case and control villages. It is clear that the abortion problem in the study villages is complex and likely due to a mix of poor husbandry practices and the presence of infectious diseases. To better understand the underlying causes of abortion, there is a need to conduct a longitudinal study involving testing for more pathogens at the household level combined with reliable data on husbandry practices.